2014
DOI: 10.1007/s10096-014-2290-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and antimicrobial susceptibility of Clostridium difficile isolated from a university teaching hospital in Japan

Abstract: Clostridium difficile infection control strategies require an understanding of its epidemiology. In this study, we analysed the toxin genotypes of 130 non-duplicate clinical isolates of C. difficile from a university hospital in Tokyo, Japan. Multilocus sequence typing (MLST) and eBURST analysis were performed for these isolates and nine strains previously analysed by polymerase chain reaction (PCR) ribotyping. Minimum inhibitory concentrations (MICs) were determined for six antibiotics, and the bacterial resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 29 publications
6
37
0
4
Order By: Relevance
“…difficile isolates of ribotypes 014/020, 056, 002, and 018 were the prevalent between 2012 and 2014 [42, 43]. Regarding Asian countries, the most common ribotypes in China have been 017, 012, and 046 [44], whereas ribotypes 018, 001, 017, and 014/020 are prevalent in Japan and Korea [11, 14]. We also found that most of the ribotypes were unique to a given hospital, with four ribotypes (AB7, AB15, AB32, and AB35) found in KNUH and seven ribotypes (AB9, AB18, AB24, AB25, AB42, AB46, and AB68) found in BPH.…”
Section: Discussionmentioning
confidence: 99%
“…difficile isolates of ribotypes 014/020, 056, 002, and 018 were the prevalent between 2012 and 2014 [42, 43]. Regarding Asian countries, the most common ribotypes in China have been 017, 012, and 046 [44], whereas ribotypes 018, 001, 017, and 014/020 are prevalent in Japan and Korea [11, 14]. We also found that most of the ribotypes were unique to a given hospital, with four ribotypes (AB7, AB15, AB32, and AB35) found in KNUH and seven ribotypes (AB9, AB18, AB24, AB25, AB42, AB46, and AB68) found in BPH.…”
Section: Discussionmentioning
confidence: 99%
“…), but almost all C. difficile FQs-resistant strains show the substitution Thr82Ile in GyrA[Ackermann et al 2001;Dridi et al 2002;Spigaglia et al 2008aSpigaglia et al , 2011Kuwata et al 2015]. In vitro experiments have demonstrated the MXF and levofloxacin (LE) exposure induce high frequency of selection for GyrA and GyrB drug-resistant mutants in previously susceptible strains…”
mentioning
confidence: 99%
“…This study revealed the molecular epidemiology of C. difficile and risk factors for the detection of toxin gene-positive strains. In a previous Japanese study, the percentage of toxin gene-positive strains and CDT gene-positive strains was 73% and 2%, respectively [10]. In other Japanese study, CDT-gene positive strains was 5% [17].…”
Section: Discussionmentioning
confidence: 79%